Storrytelling Sebagai Metode Pemahaman Mata Pelajaran Sejarah Kebudayaan Islam - Muftiyah, Al; Mashuri, Imam; Habibah, Nur Faiz (MOMENTUM : Jurnal Sosial dan Keagamaan, 2024)
This stuidy aims to eixplain thei impleimeintation of thei storyteilling leiarning meithod and to find ouit thei suipporting factors and inhibiting factors of thei storyteilling leiarning meithod in thei suibjeict of Islamic Cuiltuiral History for class VI stuideints at SDI Nuiruil Falah. Thei storyteilling meithod is a way of conveiying or preiseinting leiarning mateirial orally in thei form of storieis from thei teiacheir to stuideints. Thei storieis uiseid muist bei inteireisting, and invitei stuideints' atteintion and cannot bei seiparateid from eiduicational goals. Thei reiseiarch approach uiseid in this reiseiarch is deiscriptivei quialitativei. Thei data analysis teichniquiei uiseis quialitativei data analysis (data reiduiction, data preiseintation, and concluision) by uising thei validity of data ceirtainty (confirmability), nameily trying to einsuirei that thei data can bei guiaranteieid so that thei quiality of thei data can bei accouinteid for. Thei reisuilts of thei reiseiarch obtaineid by thei reiseiarcheir can bei concluideid that thei application of thei storyteilling meithod in thei history of Islamic cuiltuirei suibjeict for class VI stuideints at SDI Nuiruil Falah has beiein carrieid ouit in accordancei with thei planning of thei storyteilling meithod on thei mateirial of thei Caliph Uithman bin Affan